2012
DOI: 10.1209/0295-5075/100/58002
|View full text |Cite
|
Sign up to set email alerts
|

Complex networks analysis of language complexity

Abstract: -Methods from statistical physics, such as those involving complex networks, have been increasingly used in quantitative analysis of linguistic phenomena. In this paper, we represented pieces of text with different levels of simplification in co-occurrence networks and found that topological regularity correlated negatively with textual complexity. Furthermore, in less complex texts the distance between concepts, represented as nodes, tended to decrease. The complex networks metrics were treated with multivari… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 19 publications
0
34
0
3
Order By: Relevance
“…Liu and Cong [14] constructed co-occurrence networks from text in different languages and used complex network parameters for the classification (hierarchical clustering) of 14 languages, where Croatian was amongst 12 Slavic. Different applications of linguistic network analysis in NLP includes: evaluation of language complexity [15], automatic summarisation [16] and evaluation of machine translation [17], authorship attribution [18] and text quality analysis [19].…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Liu and Cong [14] constructed co-occurrence networks from text in different languages and used complex network parameters for the classification (hierarchical clustering) of 14 languages, where Croatian was amongst 12 Slavic. Different applications of linguistic network analysis in NLP includes: evaluation of language complexity [15], automatic summarisation [16] and evaluation of machine translation [17], authorship attribution [18] and text quality analysis [19].…”
Section: Related Workmentioning
confidence: 99%
“…Costa et al [15] studied the relationship between the topology of network and complexity of the text. They studied texts with different levels of simplification in cooccurrence networks and found that topological regularity correlated negatively with textual complexity.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Of special relevance to this paper, are the networked models of language and texts, which have been useful to unveil universal properties including the scale-free and small-world phenomena [22]. In practical terms, networked models have been useful to grasp several features of texts, such as quality [23], complexity [24] and authenticity [25]. Particularly, in this study, we used the so-called word adjacency model, which is a approximation of text networks formed by syntactical links [26].…”
Section: Introductionmentioning
confidence: 99%